1996
DOI: 10.1016/0010-8545(95)01216-8
|View full text |Cite
|
Sign up to set email alerts
|

Tin-based antitumour drugs

Abstract: We have been active in the synthesis and characterization of tin-based antitumour compounds for several years and we would like to summarize here the results that have already been patented(1) and that may therefore be disclosed(2). We synthesized some diorganotin 2,6-pyridinedicarboxylates.The dimethyltin compound has been found inactive in vitro, whereas the din -butyltin, di-t-butyltin and diphenyltin compounds were found more active than cisplatin(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
221
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(227 citation statements)
references
References 4 publications
4
221
0
2
Order By: Relevance
“…2,4,9,10) Up to date several articles concerning antitumor activity of organometallic tin-containing compounds have been reported. Organotin carboxylates, [11][12][13][14][15][16][17][18] organotin complexes derived of aminoacids and peptides are some examples. 9,19) As part of our interest in pentacoordinated species we recently reported the synthesis and structure of a series of pentacoordinated tin compounds.…”
mentioning
confidence: 99%
“…2,4,9,10) Up to date several articles concerning antitumor activity of organometallic tin-containing compounds have been reported. Organotin carboxylates, [11][12][13][14][15][16][17][18] organotin complexes derived of aminoacids and peptides are some examples. 9,19) As part of our interest in pentacoordinated species we recently reported the synthesis and structure of a series of pentacoordinated tin compounds.…”
mentioning
confidence: 99%
“…Following sets of titration mixture were prepared with the ratio of 10% alcohol and 90% water by keeping total volume 50mL and titrated against 0.10M NaOH solution, ionic strengths ( µ=0.05, 0.10, 0.15M) is maintained by adding different concentration of NaNO 3 …”
Section: Equipments and Measuring Techniquesmentioning
confidence: 99%
“…Chandrasekhar et al have recently reported the synthesis of organotin carboxylates having most commonly observed structure using a solventless methodology where the starting materials are ground together [11]. The only limitations of this very useful method are the relatively slower rates and the hazards associated with prolonged grinding of the reaction mixture (organotin carboxylates are known to have anti-neoplastic properties) [12]. Continuing our earlier studies on tin carboxylates derived from bulkier carboxylic acids [8a] we wish to report in this contribution a synthetic strategy that utilizes both grinding and microwave irradiation to efficiently remove the water produced in the condensation reaction between an organotin acid/oxide and 3,5-di-tert-butylsalicylic acid.…”
Section: Introductionmentioning
confidence: 99%